Socialist Patriarchy and the Limits of Reform: A Reading of Irmtraud Morgner's Life and Adventures of Troubadora Beatriz as Chronicled by her Minstrel Laura - Biddy Martin (Studies in 20th & 21st Century Literature, 1980)
Irmtraud Morgner's Life and Adventures of Troubador Beatriz is one of several important anti-patriarchal texts to come out of the GDR over the past ten years. It is a complex and ambitious attempt to elaborate the meaning of women's emancipation in a socialist society, an attempt which is structurally and thematically marked by a struggle between oppositional and orthodox approaches to questions of sexuality, knowledge and power. This particular reading of the text emphasizes the limitatons which traditional Marxist analysis and representational practices impose upon a textual field which necessarily introduces conflict and difference into the repressive stability of GDR socialism and its conventional narrative representation. Having made women's radically different desires, experiences and relationships with one another a legitimate subject, the text opens up knowledges which threaten to violate traditional political, social and sexual orders, and conventional narrative consistencies. I have attempted to read the text's transgressions and radical oppositions against the pressure of its insistently conclusive Marxism and to suggest the need for a critical re-thinking of the relations between sexuality, representation and power.
Keywords: Irmtraud Morgner; Life and Adventures of Troubador Beatriz; anti-patriarchal; GDR; DDR; women& #x27; s emancipation; socialist society; sexuality; knowledge; power; conflict; traditional political; social; sexual order; Marxism